BEHAVIOURAL AND ANTIOXIDANT PROFILE OF VENLAFAXINE TREATED ANIMAL MODEL OF DEPRESSION - ANUBHAMA KV,; DOSS VA, (International Journal of Pharma and Bio Sciences, 2014)
Venlafaxine is the first Serotonin Norepinephrine reuptake inhibitor (SNRI) and is one of the First-line antidepressants currently used owing to its rapid onset and decreased propensity to cause anticholinergic effects and cardiotoxicity. The mechanisms of psychopathology of depression are multifaceted and include evidence that oxidative stress may play an important role. In the present study the effect of Venlafaxine treatment on the antioxidant profile of Chronic Unpredictable Mild Stress induced male Wistar rats was determined and correlated with behavioural assessment following administration of Venlafaxine for 21 days. The results showed a significant decrease in sucrose consumption on stress induction, which increased significantly during Venlafaxine treatment. The period of immobility during the forced swim test was also found to be decreased with treatment, whereas the activities of enzymic and nonenzymic antioxidants were found to be significantly increased.